A proof of the existence of φ-stable sets in N-player games via Glicksberg's fixed point theorem. (2016) - Luckraz, Shravan
It is shown that if we represent the widely studied class of finite games with mixed extensions by some general abstract system, then the existence of a non-empty phi-stable set follows from Glicksberg's fixed point theorem.